Analysis of clinical and genomic profiles of therapy-related myeloid neoplasm in Korea - Jiwon Yun; Hyojin Song; Sung-Min Kim; Soonok Kim; Seok Ryun Kwon; Young Eun Lee; Dajeong Jeong; Jae Hyeon Park; Sunghoon Kwon; Hongseok Yun; Dong Soon Lee (Human Genomics, 2023)
Abstract Background Therapy-related myeloid neoplasm (T-MN) rarely occurs among cancer survivors, and was characterized by poor prognosis. T-MN has germline predisposition in a considerable proportion. Here, clinical characteristics and germline/somatic variant profiles in T-MN patients were investigated, and the findings were compared with those of previous studies. Methods A review of medical records, cytogenetic study, targeted sequencing by next-generation sequencing, and survival analysis were performed on 53 patients with T-MN at a single institution in Korea. Results The patients were relatively younger compared to T-MN patients in other studies. Our T-MN patients showed a high frequency of complex karyotypes, −5/del(5q), and −7/del(7q), which was similar to the Japanese study group but higher than the Australian study group. The most common primary disease was non-Hodgkin lymphoma, followed by breast cancer. The detailed distributions of primary diseases were different across study groups. Seven patients (13.2%) harbored deleterious presumed/potential germline variants in cancer predisposition genes (CPG) such as BRIP1, CEBPA, DDX41, FANCM, NBN, NF1, and RUNX1. In the somatic variant profile, TP53 was the most frequently mutated gene, which was consistent with the previous studies about T-MN. However, the somatic variant frequency in our study group was lower than in other studies. Adverse factors for overall survival were male sex, older age, history of previous radiotherapy, previous longer cytotoxic therapy, and −5/del(5q). Conclusion The findings of our study corroborate important information about T-MN patients. As well as a considerable predisposition to CPG, the clinical characteristics and somatic variant profile showed distinctive patterns. Germline variant testing should be recommended for T-MN patients. If the T-MN patients harbor pathogenic germline variants, the family members for stem cell donation should be screened for carrier status through germline variant testing to avoid donor-derived myeloid neoplasm. For the prediction of the prognosis in T-MN patients, sex, age, past treatment history, and cytogenetic findings can be considered.